Bioassay studies for bruchid (Callosobruchus chinensis) resistance in - SOMAPPA, JAGGAL; MOHAMMAD, NASEER; BAJPAI, G C; VERMA, S K; JOSHI, REENA (The Indian Journal of Agricultural Sciences, 2012)
The results of bioassay indicated that per cent adult emergence, mean time of adult emergence and per cent weight loss were most important parameters which helped in categorizing the genotypes into susceptible or resistant. Out of nine interspecific progenies, one of progeny UPAS120 × scarabaeiodes was found least susceptible for Callosobruchus chinensis, while other progenies in the descending order for resistance to bruchid were UPAS120 × cajanifolius, PA134 × C. scarabaeiodes, PA134 × C. acutifolius, ICPL84023 × C. cajanifolius and ICPL84023 × scarabaeiodes. Since genetic resistance is the cheapest source of resistance in managing the biotic stress, the resistant material found in this study will definitely useful in the pigeonpea improvement programme especially for bruchid resistance.